1999
DOI: 10.1002/(sici)1097-0061(199904)15:6<451::aid-yea383>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis ofHO gene in delayed homothallism inSaccharomyces cerevisiae wy2

Abstract: Saccharomyces cerevisiae wy2 exhibits a novel life cycle, with delayed homothallism caused by a defective HO gene. In this strain, gradual diploidization occurs during successive subcultures. Three amino acids of wy2 HO were different from those of wild‐type (wt) HO, which included a nonsense mutation (TAG) from Trp‐292 and two amino acid changes of His‐475 to Leu and Glu‐530 to Lys. The ho gene of heterothallic strain CG379 was also sequenced in this study. Four amino acids of ho were different from those of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…1995). In another study, the same mutation was found to reduce, but not abolish, the ability to switch mating type (Ekino et al. 1999).…”
Section: Resultsmentioning
confidence: 95%
“…1995). In another study, the same mutation was found to reduce, but not abolish, the ability to switch mating type (Ekino et al. 1999).…”
Section: Resultsmentioning
confidence: 95%
“…2). The predicted C. glabrata and K. delphensis Ho proteins have 68% sequence identity to each other and 57% identity to S. cerevisiae Ho protein and show conservation of the two LAGLIDADG endonuclease motifs and the Gly-223 residue identified as essential for mating-type switching in S. cerevisiae (16).…”
Section: Resultsmentioning
confidence: 98%
“…The prototrophic yeast deletion collection strains described above were used for both mutant screens conducted as part of this study (MATa can1Δ::STE2pr-SpHIS5 lyp1 his3 ho − ). As a surrogate for wild-type behavior, the hoΔ::kanMX strain from the deletion collection was used, although all strains have nonfunctional HO alleles containing the standard amino acid replacements found in S288C-derived strains (T189A, G223S, L405S, H475L) (44,45). Data for the analysis of changes in gene expression as the result of mild heat shock (28-36°C) were acquired using a prototrophic, CEN.PK derivative (DBY11092 MATa MAL2-8 C ) as part of a previous study (9,46).…”
Section: Methodsmentioning
confidence: 99%